2015
DOI: 10.11648/j.ijnfs.20150401.18
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Children (6-59 Months) from Food Secure and Food Insecure Households in Rural Communities of Saesie Tsaeda-Emba District, Tigray, North Ethiopia: Comparative Study

Abstract: Abstract:The aim of this study was to Assess and compare nutritional status and associated factors of 6 to 59 months old children from food secure and food insecure households in rural Kebeles of Saesie Tsaeda Emba district, Tigray, North Ethiopia. As a result, a comparative, cross sectional study was conducted on 841 children (421 from food secure and 420 from food insecure households) from February to March, 2014. Multistage sampling method was used to select Children from each kebele. Anthropometric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 10 publications
11
10
0
Order By: Relevance
“…The result of the present study is similar with that of study carried out in Tigray region of Ethiopia that shows there was statistically significant difference in stunting between food secure and food insecure households in which children from food insecure households had about 48% at higher odds to be stunted when compared to the children of food secure households [23]. Moreover, similar findings were reported from a cross-sectional study conducted on less than 5 years children from Bangladesh, Ethiopia and Vietnam where the odds of being stunted were significantly higher for children in severely food-insecure households in Bangladesh and Ethiopia while the higher odds of being stunted was higher for children in moderately foodinsecure households in Vietnam [9].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The result of the present study is similar with that of study carried out in Tigray region of Ethiopia that shows there was statistically significant difference in stunting between food secure and food insecure households in which children from food insecure households had about 48% at higher odds to be stunted when compared to the children of food secure households [23]. Moreover, similar findings were reported from a cross-sectional study conducted on less than 5 years children from Bangladesh, Ethiopia and Vietnam where the odds of being stunted were significantly higher for children in severely food-insecure households in Bangladesh and Ethiopia while the higher odds of being stunted was higher for children in moderately foodinsecure households in Vietnam [9].…”
Section: Discussionsupporting
confidence: 89%
“…In line with our analytical pathways, many studies suggest that the influence of food supply and access on nutritional status of children can be confounded by other key determinants of child nutrition, such as maternal knowledge on child nutrition and caring practices, maternal nutritional status, intra household food allocation and utilization, access to health services, and healthful environment like hygiene and sanitation [24]. However, Amaha et al, [23] reported similar finding where underweight and wasting in children had no association with household food insecurity. Other researchers also found that food insecurity had no association with wasting.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Studies from Tigray Region, Ethiopia [38] and India [46] reported similar results. The association between large family size and stunting among preschool children can be partially explained by as the number of families increased in the household, the food consumption and expenditure will also be increased.…”
Section: Discussionsupporting
confidence: 57%
“…For example, Tigray reported 52% and 46.1% prevalence of stunting among children from FIHHs and FSHHs, respectively [38], and Shewa, reported 54.2% and 46.7% among children from FIHHs and FSHHs, respectively [39]. The possible reason for these discrepancies might be the fact that as Albuko is one of the districts in which community based nutrition intervention has been implemented for a long period of time which in turn expose the community to be aware of nutritional interventions thereby it has contributing to the reduction of stunting and other forms of malnutrition in the study are.…”
Section: Discussionmentioning
confidence: 99%